Green synthesis of ag nanoparticles and their performance towards antimicrobial properties - Sunderishwary S Muniandy; S Sasidharan; Hooi, Ling Lee (Penerbit Universiti Kebangsaan Malaysia, 2019)
Green synthesis is a forthcoming trend in the nanotechnology field where classical methods of synthesis are now replaced by inexpensive and eco-friendly methods. In this study, a green method has been developed for the synthesis of silver nanoparticles (AgNPs) where AgNPs were synthesised using water-based facile hydrothermal method. Silver nitrate (AgNO3) and polyvinylpyrrolidone (PVP) were used as precursor and reducing agents to produce AgNPs. The molar ratio effect of the precursor and stabiliser, its reaction temperature and reaction time were investigated. X-ray Powder Diffraction (XRD), Field-Emission Scanning Electron Microscope (FESEM) and UV-Vis Spectrometry were used to characterise the AgNPs. The as-synthesized AgNPs with different molar ratios of the precursor to stabiliser were tested for antibacterial activities using Gram-positive bacteria (Bacillus subtilis) and Gram-negative bacteria (Escherichia coli). All the AgNPs samples exhibited antibacterial activities that were stronger against Gram-negative bacteria, as compared with Gram-positive bacteria. The diameter of the zone of inhibition (ZOI) increased with the increase of the AgNO3: PVP molar ratios. The results obtained proved that uniform AgNPs synthesized via green techniques have a high potential of influencing applications involving antimicrobial properties.